Unique N doped Sn3O4 nanosheets as an efficient and stable photocatalyst for hydrogen generation under sunlight - Balgude, Sagar; Sethi, Yogesh; Gaikwad, Aarti; Kale, Bharat; Amalnerkar, Dinesh; Adhyapak, Parag (Nanoscale, 2020)
Unique N doped Sn3O4 nanosheets have been demonstrated successfully using a facile hydrothermal method. Investigations of the triclinic phase and the impurities were performed using powder X-ray diffraction analysis (XRD) and Raman spectroscopy. The morphological analysis demonstrated a rectangular intra- and inter-connected nanosheet-like structure. The length of the nanosheets was observed to be in the range of 200-300 nm and the thickness of the nanosheets was less than 10 nm. The optical study reveals an extended absorption edge into the visible region, owing to the incorporation of nitrogen into the lattice of Sn3O4, which was further confirmed using X-ray photoelectron spectroscopy (XPS). Considering the band structure in the visible region, the photocatalytic activities of pristine and N doped Sn3O4 nanosheets for hydrogen evolution from water under natural sunlight were investigated. 4% N-Sn3O4 showed a higher photocatalytic activity (654.33 mu mol(-1) h(-1) 0.1 g(-1)) for hydrogen production that was eight times that of pristine Sn3O4. The enhanced photocatalytic activity is attributed to the inhibition of charge carrier separation owing to the N doping, morphology and crystallinity of the N-Sn3O4 nanostructures. A stable efficiency was observed for three cycles, which clearly shows the stability of N-Sn3O4.

One-pot concurrent biosynthesis of biphasic CuxO (cuprous and cupric oxide) nanoparticles using leaf extract of Eichhornia crassipes and investigation of their potent healthcare applications - Moudgil, Aliesha; Varma, Sanjana; Shinde, Manish D.; Vamkudoth, Koteswara Rao; Sarkar, Dhiman M.; Shende, Rajnigandha A.; Amalnerkar, Dinesh; Chaudhari, Bhushan P. (Emergent Materials, 2022)
Eichhornia crassipes, an aquatic weed, has been used for the one-pot quick synthesis of cuprous and cupric oxide nanoparticles in this report. The identification and validation of the formed nanoparticles were successfully done by sophisticated characterization techniques such as UV–visible spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Their biomedical interventions were assessed by their antioxidant and anticancer activities. The synthesized nanoparticles have a spherical morphology with an average diameter of 10 nm. Antioxidant assay performed showed an increasing trend in a dose-dependent manner with the percentage radical scavenging activity up to 94.70% at a much higher concentration of 1000 µg/ml. The antioxidant potential at such higher concentration is suspected to invoke a change in the cytotoxic potential of the nanoparticles which is then verified by the MTT assay. A significant cytotoxic activity against HeLa (cervical cancer) and HCT 116 (colorectal carcinoma) cell lines was detected with noted IC50 values of 17.17 and 13.70 µg/ml respectively. The conclusive findings obtained are enough to substantiate the use of these nanoparticles in biomedical areas specifically in anticancer treatment due to their high toxicities. The hazards imposed by Eichhornia crassipes can be alleviated by using them as biofactories for the synthesis of a variety of nanomaterials. This helps in curbing the water pollution issues as well as the developing synthesis protocols for robust and stable nanoparticles.

Gold nanorods (GNRs): a golden nano compass to navigate breast cancer by multimodal imaging approaches - Varma, Sanjana; Bamb, Aagam Lalit; Haldar, Niladri; Gajbhiye, Virendra; Amalnerkar, Dinesh; Chaudhari, Bhushan Pradosh (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2025)
The ongoing rise in the incidences of breast cancer cases has concerned medical and scientific personnel around the world. Adequate treatment of cancer predominantly relies on the pertinent diagnosis of the type of cancer as well as other molecular and cellular details at the initial stage only. Surprisingly, up till now, there is no single, self-reliant imaging modality that helps to systematically find out the anatomical and functional events taking place inside the body. This resulted in the advent of the multimodal imaging concept, which encompasses the integration of complementary imaging modalities by designing multimodal imaging probes. Gold nanorods (GNRs) are extremely popular and effective nanoparticles for multimodal bioimaging due to their unique properties. Researchers have designed varieties of stable and biocompatible GNR-based probes for targeted and nontargeted multimodal imaging of breast cancer. However, there is a lack of investigations on the in vivo fate and the toxicity of GNRs. Thus, their preclinical to clinical translation can be attained by comprehensively determining the in vivo fate and toxicity of GNRs. The review provides details about the GNRs-based nanoprobes fabricated so far for breast cancer imaging, which, by consequent studies, can be taken up to clinical usage.
Keywords: Breast cancer; Gold nanorods; imaging probes; Multimodal Imaging